The three great Soviet composers and Mstislav Rostropovich : talent, music and politics in the Soviet Union : a thesis submitted to Massey University and Victoria University of Wellington in partial fulfillment of the requirements for the degree Master of Musical Arts in Violoncello Performance, New Zealand School of Music - Gijsbers, Lucy (Massey University, 2014)
Mstislav Rostropovich, the most famous cellist of the second half of the twentieth century, had a close relationship with Dmitri Shostakovich, Sergei Prokofiev, and Mieczyslaw Weinberg. These three composers are hailed by some as the three greatest Soviet composers of the twentieth century,1 although in New Zealand and much of Western society little of Weinberg's music has been played. They lived under the reign of Joseph Stalin, and were greatly restricted in what they could compose. Whilst Weinberg in 1953 was arrested in Russia for 'Jewish bourgeois nationalism', the music of Shostakovich and Prokofiev was banned in 1948; deemed antidemocratic and too formalistic. All three composers wrote cello works for Rostropovich. Whilst Shostakovich's cello works are regularly performed - most likely because Rostropovich championed this composer's works above all others - Weinberg's cello works are not. Prokofiev's Sinfonia Concertante used to be avoided by cellists because of its difficulty, but in recent years it has rapidly gained in popularity. Weinberg's music is slowly gaining recognition for its worth. Rostropovich did not even play some of Weinberg's cello works which were dedicated to him, as he had an altercation with the composer. This essay explores the relationship between the four musicians, the influence they had on one another, and their reaction to the political climate in the Soviet Union and elsewhere. Rostropovich in particular was very politically active, and used his fame to influence politics. Ultimately the cellist was awarded over fifty prizes for both musical and humanitarian efforts. [No abstract supplied. Taken from Introduction.]
Keywords: Mstislav Rostropovich; Mieczyslaw Weinberg; Moiseĭ Vaĭnberg; Dmitri Shostakovich; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Music; Music; Composers; Cellists; Soviet Union; 20th century